Teaching true love to a sex-at-13 generation : the ultimate guide for parents - Ludy, Eric.; Ludy, Leslie (Nashville, Tenn. : W Pub. Group, 2005)
"Guide for talking to teenagers today about abstaining from sex until marriage"--Provided by publisher.
Includes bibliographical references.
Keywords: Chastity; Christian teenagers -- Religious life; Child rearing -- Religious aspects -- Christianity; Sexual abstinence -- Religious aspects -- Christianity; Sex instruction for teenagers -- Religious aspects -- Christianity